2020
DOI: 10.1007/s40123-020-00296-0
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Recent Developments in Idiopathic Intracranial Hypertension

Abstract: There is increasing evidence and appreciation of idiopathic intracranial hypertension (IIH) in medicine. The pathological processes underlying raised intracranial pressure are being studied, with new insights found in both hormonal dysregulation and the metabolic neuroendocrine axis. These will potentially lead to novel therapeutic targets for IIH. The first consensus guidelines have been published on the investigation and management of adult IIH, and the International Headache Society criteria for headache at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 101 publications
1
34
0
1
Order By: Relevance
“…When compared to the primary care data in the UK, which have previously been published, the incidence over corresponding years is similar. [ 4 ] Likewise, within this cohort there are patients over the age of 65 years ( Figure 2 A), which is not typical of the known phenotype of IIH, described by the IIH literature as a disease that occurs with the major risk factor being weight gain in women of working age [ 1 , 2 , 7 ]. A recent retrospective case series analysis of IIH above the age of 65 years reported that the diagnosis was more commonly seen in males, with incidentally found papilloedema; they had fewer headaches, and on investigation had lower lumbar puncture opening pressure, as compared to IIH controls below the age of 50 years [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When compared to the primary care data in the UK, which have previously been published, the incidence over corresponding years is similar. [ 4 ] Likewise, within this cohort there are patients over the age of 65 years ( Figure 2 A), which is not typical of the known phenotype of IIH, described by the IIH literature as a disease that occurs with the major risk factor being weight gain in women of working age [ 1 , 2 , 7 ]. A recent retrospective case series analysis of IIH above the age of 65 years reported that the diagnosis was more commonly seen in males, with incidentally found papilloedema; they had fewer headaches, and on investigation had lower lumbar puncture opening pressure, as compared to IIH controls below the age of 50 years [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changing awareness of the condition due to publication of the IIH guidelines [ 23 , 24 ] and emerging evidence [ 1 , 2 ] could have influenced the trends, in particular, the recommendation that CSF shunting should only be performed for sight threatening disease and not headache symptoms. Similarly, recommendations for medical headache management could have possibly reduced the number of those who had previously been admitted for repeat lumbar punctures or sought surgery for management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Idiopathic intracranial hypertension (IIH) causes challenging headaches, visual loss, and reduced quality of life [ 1 ]. Hospital costs for IIH admissions have been found to be four times greater than for a general population-based per person admission [ 2 ].…”
Section: Introductionmentioning
confidence: 99%